Determinant factor of the quality of financial statements and performance of the government by adding contextual factors - Nirwana; Haliah (Asian Journal of Accounting Research, 2018)
The purpose of this paper is to re-test the determinant factors of the quality of financial statements and performance of the government by adding contextual factors, such as personal factor, system/administrative factor and political factor, that may affect the quality of financial statement information and performance of the government. Personal factor is proxied to the competencies that affect the quality of financial statements and performance. Social administrative factor is proxied on the regulations and presentation of quality financial statements.The analysis unit in this study was conducted at the organizational level. The research object was in South Sulawesi Province. This was a descriptive and verificative research with survey technique. Based on the objectives of the research, this is an explanatory research. The research method used was explanatory survey with quantitative approach. The population of this research was proxied to the Regional Unit Organization (Organisasi Perangkat Desa) which compiled the financial statements in South Sulawesi Provincial Government consisted of 803 units of Local Government Agencies (Satuan Kerja Perangkat Daerah). The purposive sampling technique was chosen under the following criteria: the regional government whose financial statement has been audited by Badan Pemeriksa Keuangan; the regional government whose financial accountability report has been evaluated by Indonesiaâ€™s Agency for Financial and Development Supervision (Badan Pengawasan Keuangan dan Pembangunan). In line with the criteria mentioned above, the minimum samples required for 26 observations/indicators are 5Ã—26=130 respondents. The sample size met the minimum sample requirement of 5 for each group (cell) (Hair et al., 2006, p. 112).Personal factors competence affects the financial statements quality. The high personal factors competence will affect on the high financial statements quality. System/administration factors regulation affect the financial statement quality. The high system/administration factors regulation will affect on the high financial statements quality. Political factors affect the financial statements quality. The high political factors will affect on the high financial statements quality. Personal factor competence has no direct effect on the performance. The high personal factor competence will not affect the high or low of the performance. However, there is a significant indirect effect between personal factor competence on performance through the financial statements quality which means that higher personal factor competence will lead to higher performance through financial statements quality. System/administration factor regulation is not directly affects the performance. The high system/administration factor regulation will not affect on the high or low of the performance. However, there is a significant indirect effect between system/administration factor regulation on performance through the financial statements quality which means that higher the system/administration factor regulation will lead to higher performance through financial statements quality. Political factors is not directly affects the performance. The high political factors will not affect the high or low of the performance. However, there is a significant indirect effect between political factors on performance through the financial statements quality which means that the higher the political factor, it will leads to higher performance through the financial statements quality. Financial statements quality affects the performance. The high financial statements will affect on the performance.The research issues raised are the increasing public demands for the government services and accountability, while on the other hand the government is faced with the report and financial quality that are below the expectation. This issue is a national strategic issue, leading this research to aim at providing guidelines that can help the regional government to formulate operational policies and strategies of the quality improvement of financial statement and performance of the regional government.